International Entrepreneurship by Indigenous Peoples in the United States and Canada - Bull, Jesse (Journal of Comparative International Management, 2024)
Native Americans and First Nations face many economic disparities. Despite a long history of international entrepreneurship, the effects of colonialization persist and present many hurdles to international entrepreneurship in Indian Country. Exporting by Native-owned businesses is associated with higher average payroll per employee and having more employees (Gresser 2022). Access to education and financing are significant obstacles. While policy changes could have a significant impact, assistance in exporter-specifictraining, education, and mentoring can have strong effects.